Economic resources and corporate social responsibility - Sun, Xian; Gunia, Brian C. (Journal of Corporate Finance, 2018)
Our research suggests that firms condition their CSR policies on the availability of economic resources. Using the value of a firm's real estate as a measure of exogenous shocks on the firm's economic resources, we show that increases in resources reduce CSR concerns, while decreases in resources increase CSR concerns. The relative impact of resource availability on CSR concerns, however, depends on several organizational variables that influence a firm's preferences for CSR investments. Furthermore, we show that firm reactions to increases and decreases in resources are not symmetric: resource gains reduce CSR concerns, but resource losses increase CSR concerns even more markedly. Overall, these results suggest that firms may treat CSR decisions in much the same way as other investment decisions.